Biocatalysts: Isolation, identification, and immobilization of thermally stable lipase onto three novel biopolymeric supports - Elnashar, Magdy; Mostafa, H.; Morsy, N.; Awad, G. (2013)
Lipase, one of the most important and versatile industrial enzymes, has been isolated, identified, and immobilized onto three novel supports prepared based on our US patent (US20110076737). Nine fungal isolates were cultivated, and maximum lipase activity of 285 U/mL was achieved from the fungal isolate identified as Rhizopus oryzae GF1. The enzyme was shown to be thermally stable at 50 C for 210 min. Three different environmentally friendly biopolymers prepared according to our US patent have been used to immobilize covalently the lipase from Rhizopus oryzae GF1. The structures of the gel beads; grafted alginate, carrageenan and alginate-carrageenan; have been proved by the FTIR. The best formulation, alginate-carrageenan, covalently immobilized 183.5 U/g lipase and was further optimized to load 223 U/g lipase. The immobilization process increased the operational temperature from 30 to 50 C compared to the free enzyme. The hydrolysis of oil using the free and the immobilized lipase was achieved at the same time, 90 min, which reflects no diffusion limitation. The shelf stability showed that the immobilized enzyme retained full activity for over 9 weeks at 4 C, whereas the free enzyme lost 80% of its initial activity after 4 weeks. The reusability test proved the durability of the grafted beads for 20 cycles with a retention of 97% of the immobilized enzyme activity compared to 23% by other authors after the 10th use. © 2013 American Chemical Society.